Circulating immune cells and vitiligo: a bidirectional two-sample Mendelian randomization study - Xin, Yu; Yuan, Tao; Wang, Jun (Frontiers in Immunology, 2024)
The pathogenesis of vitiligo remains elusive. Emerging evidence suggests that vitiligo is an immune-mediated disorder, in which a plethora of immune cells play pivotal roles. However, the association between circulating immune cells and vitiligo continues to be enigmatic.We extracted single nucleotide polymorphisms (SNPs) associated with immune circulating cells at a genome-wide significance level from the BLOOD CELL CONSORTIUM's genome-wide association study (GWAS) dataset. Summary data for 385,801 cases of vitiligo were obtained from a large-scale Finnish genome-wide association study (ncases=292, ncontrols=385,509). The inverse variance weighted (IVW) method was employed as the primary analytical approach for Mendelian randomization (MR) analysis. Additionally, heterogeneity was assessed using Cochran's Q value, and horizontal pleiotropy was evaluated using MR-Egger 、Mendelian Randomization Pleiotropy RESidual Sum and Outlier and leave-one-out analyses.Results: The risk of vitiligo was found to increase with the elevation of 4 circulating immune cells, as evidenced by the odds ratios (ORs) and 95% confidence intervals (CIs):